Recursion Operators and Tri-Hamiltonian Structure of the First Heavenly Equation of Plebanski - Sheftel, Mikhail B.; Yazici, Devrim (NATL ACAD SCI UKRAINE, INST MATH, 2016)
We present first heavenly equation of Plebanski in a two-component evolutionary form and obtain Lagrangian and Hamiltonian representations of this system. We study all point symmetries of the two-component system and, using the inverse Noether theorem in the Hamiltonian form, obtain all the integrals of motion corresponding to each variational (Noether) symmetry. We derive two linearly independent recursion operators for symmetries of this system related by a discrete symmetry of both the two-component system and its symmetry condition. Acting by these operators on the first Hamiltonian operator J(0) we obtain second and third Hamiltonian operators. However, we were not able to find Hamiltonian densities corresponding to the latter two operators. Therefore, we construct two recursion operators, which are either even or odd, respectively, under the above-mentioned discrete symmetry. Acting with them on J(0), we generate another two Hamiltonian operators J(+) and J(-) and find the corresponding Hamiltonian densities, thus obtaining second and third Hamiltonian representations for the first heavenly equation in a two-component form. Using P. Olver's theory of the functional multi-vectors, we check that the linear combination of J(0), J(+) and J(-) with arbitrary constant coefficients satisfies Jacobi identities. Since their skew symmetry is obvious, these three operators are compatible Hamiltonian operators and hence we obtain a tri-Hamiltonian representation of the first heavenly equation. Our well-founded conjecture applied here is that P. Olver's method works fine for nonlocal operators and our proof of the Jacobi identities and bi-Hamiltonian structures crucially depends on the validity of this conjecture.
Keywords: first heavenly equation; Lax pair; recursion operator; Hamiltonian operator; Jacobi identities; variational symmetry; DIFFERENTIAL GEOMETRY; PARTNER SYMMETRIES; HYDRODYNAMIC TYPE; SYSTEMS; METRICS; Mathematics; Physics